The method of estimating the employment potential of migrant workers - R. R. Kugushev (Путеводитель предпринимателя, 2020)
The article proposes an innovative method of estimating the employment potential of migrant workers arriving in the Russian Federation, by identifying their professional competences, business and personal qualities, peculiarities of socialization. The introduction of this technique will facilitate professional and social adaptation of migrants and their employment opportunities on the territory of our country.